Meta-Analysis: Effectiveness of Web-Based Intervention to Increase Physical Activity in Older People - Gina Fazrina; Hapsari Cahyaningrum (Journal of Health Promotion and Behavior, 2022)
Background: The increasing global population of older people and the trend of life expectancy make the discussion of physical activity an urgent urgency, given its role in preventing various non-communicable diseases and increasing life expectancy. Web-based intervention is believed to be an intervention that can change habits related to physical activity in older people. This study aimed to find out whether web-based intervention is effective in increasing physical activity for older people.Subjects and Method: This research is a meta-analysis based on the PRISMA flow diagram. The article search process is carried out through journal databases, in the form of: Google Scholar, PubMed, and ResearchGate. Keywords to search for articles are: "Aged" OR "older adult" OR "elderly" AND "Exercise" OR "exercise" OR "physical activity" OR "physical activities" OR "physical exercise" OR " physical exercises" OR "physical fitness" AND "Internet-Based Intervention" OR "internet-based interventions" OR "web-based interventions" OR "web-based interventions" OR "online interventions" OR “internet intervention” OR “mobile health” OR “mhealth” OR “telehealth” OR “ehealth” AND “randomized control trials” OR “randomized control trials” OR “RCT”. The articles included are study design randomized control trial (RCT), articles with research subjects older people aged 50 years and over, and the intervention used is web-based intervention. Articles that meet the criteria are then analyzed using the Revman 5.3 application.Results: A total of 9 articles were found from the Netherlands, Spain, England, Belgium, and Sweden. The data collected showed that web-based intervention increase physical activity in older people, and it was statistically significant (SMD= 0.78; 95% CI=0.15 to 1.41; p= 0.020).Conclusion: Web-based intervention is effective for increasing physical activity for older people who are more than 50 years old.Keywords: web-based intervention, physical activity, older people, meta analysis.Correspondence:Gina Fazrina. Study Program of Physiotherapy, School of Health Sciences Cirebon. Jl. Brigjen Dharsono No. 12B ByPass Cirebon 45153, West Java, Indonesia. Email: ginafazrina@gmail.com. Mobile: +681212533833.Journal of Health Promotion and Behavior, (2022), 07(01): 55-66DOI: https://doi.org/10.26911/thejhpb.2021.07.01.06